The Fragile tropics of Latin America : sustainable management of changing environments - Nishizawa, Toshie, 1929-; Uitto, Juha I. (United Nations University Press, 1995)
"Amazonia and adjacent lands have tremendous environmental variations, and approaches to the sustainable management of these fragile lands must be different. Geographers Hiraoka, Nishizawa, Sternberg, and Yagasaki have important contributions among the 14 articles"--Handbook of Latin American Studies, v. 57.